Unplanned Exposure to Genetically Modified Organisms: Divergent Responses in the Global South - Jennifer Clapp (The Journal of Environment and Development, 2006)
This article examines the divergent political responses to unplanned exposure to genetically modified organisms (GMOs) in the Global South. Although scientific and domestic political considerations have some relevance to explaining different positions among developing countries, trade considerations appear to be a principal driver of GMO policy. This consideration is strikingly clear when we compare the different responses to unplanned GMO imports in Mexico/Central America with that in Africa. When trade and environment interests converge, as was the case in Africa, the strong policy stance, in this case against the import of GMOs, was clear and swift. In the cases of Mexico and Central America, the trade and environment interests did not overlap, and this has resulted in a weak government response and incremental policy shifts, in this case toward a pro-GMO stance.